Płeć kulturowa i polskie elity administracyjne = Gender and Polish administration elites - Post, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents qualitative analysis of statements made by representatives of central administration elites. These statements were collected while 50 in-depth open interviews, carried out in 2013. The analysis covers selected parts of culture of this environment - narratives about normative visions of a good state and ideas of the best qualities of good officials. Its aim is to answer the question if senior civil servants, women and men, understand them in similar or different way.
Keywords: sex; gender; normative patterns; civil servants; płeć; wzorzec normatywny; Urzędnicy - Polska